Analysis of different operation modes for inertia motors - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (ACTUATOR 2012 Conference Proceedings)
Piezoelectric inertia motors, also known as ``stick-slip-drives'', use the inertia of a body to drive it by means of a friction contact in small steps. While these steps normally involve stiction and sliding, the motors can also operate in ``slip-slip'' mode without any phase of static friction. In this contribution, a one degree of freedom model of an inertia motor driven by an ideal actuator is analysed. Start-up and constant velocity operation of the motor are investigated and appropriate quantities to compare ``stick-slip'' and ``slip-slip'' operation are determined. Different aspects such as velocity, uniformity of motion, load capacity, robustness, efficiency, and wear are considered. The analysis allows both modes to be applied advantageously in different applications and can widen the field of application of piezoelectric inertia motors. Motor designers are enabled to choose the appropriate mode of operation and the best drive parameters for their individual applications.
Keywords: Piezoelectric Inertia Motors; Drive Signals; Stick-slip; Slip-slip